Factors associated with delayed neurologic improvement after complete endovascular reperfusion in anterior and posterior ischemic stroke - Park, Sangil; Kwon, Boseong; Chang, Jun Young; Song, Yunsun; Lee, Deok Hee; Ha, Sang Hee; Kim, Bum Joon (Frontiers in Neurology, 2025)
BackgroundMechanisms underlying delayed neurological improvement (DNI) after endovascular thrombectomy (EVT) in patients with anterior (ACS) and posterior circulation stroke (PCS) may differ. This study aims to compare the factors associated with DNI in patients with ACS and PCS.Materials and methodsData of patients who underwent EVT with National Institute of Health Stroke Scale (NIHSS) score more than 6 and achieved successful reperfusion were retrospectively analyzed. DNI was defined as achieving favorable functional outcomes at 90 days, even without early neurological improvement. The factors associated with DNI in patients with ACS and PCS were investigated.ResultsA total of 241 patients were included. The proportions of DNI (30.8% vs. 20.0%; p = 0.184) were not significantly different between patients with ACS and PCS. In patients with ACS, absence of atrial fibrillation (aOR = 0.500; 95% CI, 0.264–0.945; p = 0.033), statin use (aOR = 2.842; 95% CI, 1.174–6.882; p = 0.021), lower NIHSS score after 24 h (aOR = 0.816; 95% CI 0.757–0.880; p < 0.001), and shorter onset-to-door time (aOR = 0.999; 95% CI, 0.998–1.000; p = 0.025) were significantly associated with DNI. In patients with PCS, male sex (aOR = 31.809; 95% CI, 1.816–557.074; p = 0.018) and lower initial NIHSS scores (aOR = 0.626; 95% CI, 0.410–0.957; p = 0.031) were significantly associated with DNI.ConclusionThe proportions of DNI were similar in patients with ACS and PCS. However, the factors associated with DNI were different between the two groups.